“Virtuous Hatred” of Oppressive Institutions: William Ray’s Republican Patriotism in His Account of the American-Tripolitan War (1808) - Lofti Ben Rejeb (Close Encounters in War Journal)
This study examines William Ray’s Horrors of Slavery (1808), a unique and underexplored account of the American-Tripolitan War (1801-1805), and the broader social, political, and cultural issues of the early American Republic. Through his narrative, Ray critiques the domestic institutions of debtor’s prison, class privilege in the US Navy, and slavery, which he views as antithetical to republican ideals. Drawing on his personal experiences as a prisoner of war and as a marginalized citizen, Ray contrasts the oppressive practices of his own country with those of Tripolitan society to highlight systemic injustices and call for reform. He leverages republican patriotism to blend autobiography and socio-political critique. His narrative conveys the aspirations and challenges of a nascent republic struggling to align national identity and citizenship with its foundational ideals of justice and equality. Its continuing relevance permeates today’s culture wars.